2019
DOI: 10.1088/1538-3873/ab33c5
|View full text |Cite
|
Sign up to set email alerts
|

First Radial Velocity Results From the MINiature Exoplanet Radial Velocity Array (MINERVA)

Abstract: The MINiature Exoplanet Radial Velocity Array (MINERVA) is a dedicated observatory of four 0.7 m robotic telescopes fiber-fed to a KiwiSpec spectrograph. The MINERVA mission is to discover super-Earths in the habitable zones of nearby stars. This can be accomplished with MINERVA's unique combination of high precision and high cadence over long time periods. In this work, we detail changes to the MINERVA facility that have occurred since our previous paper. We then describe MINERVA's robotic control software, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…The two EXPRES RV methods are also internally consistent, with the forward model producing a slightly more favorable RMS. Finally, we note that the RMS of the EXPRES fit residuals approximately matches that of the HARPS DRS, with the EXPRES fit returning parameters more comparable with literature values (Bedell et al 2019;Wilson et al 2019;Wang & Ford 2011).…”
Section: Initial Results -Hd 217014supporting
confidence: 83%
“…The two EXPRES RV methods are also internally consistent, with the forward model producing a slightly more favorable RMS. Finally, we note that the RMS of the EXPRES fit residuals approximately matches that of the HARPS DRS, with the EXPRES fit returning parameters more comparable with literature values (Bedell et al 2019;Wilson et al 2019;Wang & Ford 2011).…”
Section: Initial Results -Hd 217014supporting
confidence: 83%
“…We present a joint analysis of 377 RV observations of the HD 217107 system spanning 20.3 years. The 42 new measurements presented here, obtained with the MINERVA telescope array (Swift et al 2015; Wilson et al 2019), extend the total published observational time baseline by almost 5 years. We confirm the existence of the outer companion, HD 217107 c, and refine the orbital solutions for both components.…”
Section: Introductionmentioning
confidence: 52%
“…MINERVA observed HD 217107 between May 2016 and November 2018, and the derived RV measurements are reported in Table 1. The MINERVA observatory, which is described in more detail in Swift et al (2015) and Wilson et al (2019), has been demonstrated to achieve an RV precision of σ RV ∼ 2 m s −1 on bright RV standard stars. The four telescopes are fiber‐coupled to a KiwiSpec echelle spectrometer with a resolution of R ∼ 84,000 and a spectral coverage of approximately 500–600 nm.…”
Section: Datasetsmentioning
confidence: 99%
“…While MINERVA is typically calibrated with an iodine cell, we removed it during these exposures to increase throughput. Wilson et al (2019) showed that the vacuum-stabilized, temperature-controlled spectrograph is stable on ∼year-long timescales, and so we did not expect significant variation of the spectrograph during the night. An approximate wavelength solution for the DT analysis was derived from archival thorium argon exposures.…”
Section: Minerva Spectroscopymentioning
confidence: 79%
“…We also obtained 37 1800s spectroscopic exposures of KELT-24 using the MINiature Exoplanet Radial Velocity Array (MINERVA) during the entire night beginning UT 2019 March 31, of which 17 exposures were taken during the transit of KELT-24 b. MINERVA is an array of four PlaneWave CDK700 0.7 m telescopes located at Mt. Hopkins, Arizona (Swift et al 2015;Wilson et al 2019). The four telescopes simultaneously fiber feed an R=80,000 KiwiSpec spectrograph Gibson et al 2012), so each exposure contains a spectrum from the four telescopes, each covering roughly 500-630 nm.…”
Section: Minerva Spectroscopymentioning
confidence: 99%